Caribbean bamboo craft to Asia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Saint Vincent and the Grenadines exports $3000 worth of bamboo craft products to Taiwan. And the future looks promising. The bamboo craft project is a joint venture of the Saint Vincent Community Development Department and the Agricultural...